“Houd moed: Kijk naar Nederland. / Kijk naar zijn vorstin! Je bent niet langer wees.”: Het “Hongaarse raam” in het Nederlandse koninklijke paleis - Réthelyi, Orsolya (Acta Neerlandica, 2017)
“Do not lose heart: Look at The Netherlands. / Look at its queen! You are no longerorphaned.”: The Hungarian window in the Dutch royal palace During a festive gathering on 21 December 1923 in the Dutch Royal Palace of Noordeinde in The Hague, a small group of delegates from the Hungarian-Dutch Society from Hungary presented a stained-glass window as a gift to Queen Wilhelmina for the 25th anniversary of her ascension to the Dutch throne. The magnificent stained-glass window in Art Nouveaustyle (202 x137 cm) made by Miksa Róth and Sándor Nagy, with an unconventional representation of the queen was given to her as a token of gratitude for the relief project arranged for children after the First World War. According to the information of the National League of Child Protection, between 1920 and 1930 28,563 Hungarian children from impoverished families were taken to the Netherlands for a holiday with Dutch foster parents. The window is kept today on the first floor of the west wing of the Palace, but the event and its significance is largely forgotten in the historiography of Hungarian ‒ Dutch relations. In this article, the pieces of the puzzle concerning the artistic object itself, the historical circumstances of the gift-giving, the intermediaries and the symbolic message are assembled, to reveal the working and complexity of cultural transfer. It is argued that the metaphor of Queen Wilhelmina, as the mother of the Hungarians, articulated on different levels of symbolic representation and communication can be seen not only as a sign of gratitude. This image should also be understood as an unspoken wish that the apolitical objectives of the relief actions would also indirectly support a political agenda, and that the personal and institutional contacts would lead to greater understanding of the Hungarian efforts to moderate the excessive punishment under which the country was suffering as result of the Treaty of Trianon.